Effect of Hydrothermal Coupling on Physical and Dynamic Mechanical Properties of Sandstone - Rong-rong Zhang; Pu Yuan (Advances in Civil Engineering)
Split-Hopkinson pressure bar (SHPB) tests were conducted for sandstone after recurrent heat-cool (H-C) cycles. Physical and mechanical properties, damage, and fracture characteristics of sandstone after the H-C cycle were explored. Additionally, the damage variable and release rate of damage strain were defined to describe the damage degree of the sandstone specimen after recurrent H-C cycles. Finally, the relationship between mass fractal dimension of fragmentation and cycling number was discussed. Results show that the P-wave velocity and density decrease with the increase of cycling number, while the porosity increases. It was found that the dynamic compressive strength and relative elastic modulus decrease with the increase of cycling number. 20 cycles is the critical point for the low temperature (L-T) group and moderate temperature (M-T) group, while it is 4 cycles for the high temperature (H-T) group. With the increase of cycling number, both the damage variable and release rate of damage strain of rock increase, while the destruction degree of sandstone becomes greater, and the corresponding fragments show more evenly.